2009
DOI: 10.1152/ajprenal.00011.2009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delays consistent with cochlear hypothyroidism contribute to failure to develop hearing in mice lacking Slc26a4/pendrin expression

Abstract: P. Developmental delays consistent with cochlear hypothyroidism contribute to failure to develop hearing in mice lacking Slc26a4/pendrin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 64 publications
3
65
0
Order By: Relevance
“…I -is a known in vitro exchange substrate of pendrin (25), and its concentration probably rises soon following the onset of type 2 deiodinase activity in the late embryonic cochlea (26). Cochlear concentrations and mechanism of I -homeostasis are unknown but, if there were not a mechanism to disperse I -, an excess could conceivably exert a toxic effect on cells within the cochlea, inhibit deiodinase reaction(s) leading to cochlear hypothyroidism (27), or produce a combination of these effects. Finally, the dependence of renal Na + reabsorption on luminal HCO 3 -secretion and alkalinization by pendrin (28) raises the possibility of an analogous role in embryonic endolymph.…”
Section: Discussionmentioning
confidence: 99%
“…I -is a known in vitro exchange substrate of pendrin (25), and its concentration probably rises soon following the onset of type 2 deiodinase activity in the late embryonic cochlea (26). Cochlear concentrations and mechanism of I -homeostasis are unknown but, if there were not a mechanism to disperse I -, an excess could conceivably exert a toxic effect on cells within the cochlea, inhibit deiodinase reaction(s) leading to cochlear hypothyroidism (27), or produce a combination of these effects. Finally, the dependence of renal Na + reabsorption on luminal HCO 3 -secretion and alkalinization by pendrin (28) raises the possibility of an analogous role in embryonic endolymph.…”
Section: Discussionmentioning
confidence: 99%
“…Pendrin has been proposed as the protein mediating the step of iodide export from the cell into the follicular lumen, i.e., of iodide crossing the thyrocyte's apical membrane (3). However, several arguments indicate that pendrin is not critical for this transport (38,44) as mice deficient for pendrin are euthyroid (4,6,42) and patients affected by the Pendred syndrome, i.e., homozygotic pendrin inactivation, may develop goiters in iodine-deficient conditions but usually not before the second decade of life (3). Another pathway for iodide transport across the apical membrane must therefore be considered, and the definition of its identity and hormonal responsiveness constitutes the aim of the present study.…”
mentioning
confidence: 99%
“…Pendred syndrome, an autosomal recessive disorder, is mainly characterized by deafness, but some patients also present with hypothyroidism (63). No thyroid phenotype has been reported for Slc26a4 KO mice (64), suggesting that pendrin plays a non-essential role in iodide transport, at least in the mouse, and that alternate transporters, most likely the Ca 2+ -activated ion channel Anoctamin-1, can mediate apical iodide efflux (1,2). Using Thyr-IL-4 transgenic mice, this study showed for the first time an IL-4-dependent induction of Slc26a4 transcription, which was associated with increased apical expression of pendrin.…”
Section: Discussionmentioning
confidence: 99%